An anti-inflammatory bundle may help avoid opioids for low-risk outpatient procedures. Issue 1 (January 2023) - Dbeis, Rachel; Assani, Khadij; Fadaee, Negin; Huynh, Desmond; Khader, Ali; Towfigh, Shirin
Background: Currently, over half of drug overdose deaths are due to opioids. Opioid alternatives may be prescribed to help curb the opioid epidemic. However, little is known about their efficacy for acute postoperative pain. Methods: We studied patients who underwent low-risk outpatient surgery. Perioperatively, all patients were started on an anti-inflammatory bundle consisting of multimodal pain remedies. Opioids were available to the patients postoperatively. Pain scores and opioid use were recorded. Results: Over 18 months, 120 patients underwent low-risk outpatient surgery and all used the anti-inflammatory bundle. All patients had a significant decrease in postoperative pain scores (p = 0.001). There was no significant difference in postoperative pain scores between those who followed the anti-inflammatory bundle alone and those who also used opioids (mean 2.2 vs 3.1/10). Twenty-five (21%) patients were using opioids preoperatively and 50 (42%) postoperatively. Of those using opioids preoperatively, six (24%) patients used the anti-inflammatory bundle alone and avoided opioids postoperatively. Conclusions: For 58% of our patients, an anti-inflammatory bundle alone provided adequate pain control after a low-risk outpatient operation, such as hernia repair. Our practice uses the anti-inflammatory bundle for all patients. Our goal is to reduce both the need for opioids and the surgeon's contribution to the opioid epidemic.